Writing news features - Masterton, Murray. (2008)
After the struggles and justifications of interpretive journalism, working out the requirements for a news feature article seems to be easy. For many it is, for others the ease is a cruel deception. Too many reporters who are asked to expand their news reports into feature material consider it as just that, a simple, uncomplicated expansion. That is not what a feature is, and that is why feature writing seems to be confined to a few people on every staff. I would be surprised if the situation is different in Southeast Asia. It shouldn't be a surprise to find that most reporters like most to report. They thrive on the pressure of gathering and writing the elements of a report to a tight deadline. Give them more time to gather more material for a backgrounding article and they are lost. They either can't or won't do it, or they have to rethink the whole purpose of their journalism.